PROSES AKUISISI PERUSAHAAN: STRATEGI, TANTANGAN, DAN DAMPAKNYA BAGI KINERJA KEUANGAN PERUSAHAAN - Nabbal, Faesha; Afifah, Annisa Nur; Panggiarti, Endang Kartini (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This research was conducted with the aim of examining the acquisition process in the company, which can be seen from the strategies that the company must carry out, the challenges faced by the company and the impact on the company’s financial performance itself. This research was conducted using a qualitative method, namely literature review. The data sources obtained are secondary data, from previous studies and relevant literature sources. The research conducted resulted in the outcome that acquisitions are an effective strategy that can be used by companies to increase company value. In the acquisition of the company there are challenges that must be faced by the company and the impact on the company’s financial performance.